Analisis Interaksi Obat Antihipertensi pada Pasien di Rumah Sakit Umum Royal Prima Marelan - Janice Tjandra; Razoki Lubis; Novitaria Br Sembiring (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Hypertension is a chronic disease that often attacks the elderly and can cause serious complications, including stroke and heart disease. This study aims to evaluate the use of antihypertensives and analyze drug interactions based on severity in hospitalized patients at RSU Royal Prima Marelan. The research method is descriptive retrospective of patient medical records in 2024. The results showed that the majority of patients were women (62.5%) aged 60–74 years (50%). The use of a combination of two antihypertensive drugs was most commonly found (40%), with the combination of amlodipine and candesartan being the most frequently used. The severity of the most drug interactions was in the moderate category (82.35%), followed by major (10.50%) and minor (7.14%). The most significant interactions occurred in the combination of candesartan and spironolactone (major), and amlodipine and bisoprolol (moderate).